Confrontation in ‘Confrontation’: A Multimodal Analysis of Bob Marley’s Lyrics - Cosmas Rai Amenorvi (Journal of English Language Teaching and Linguistics, 2019)
This study investigates multimodally the theme of confrontation in Bob Marley’s posthumous Confrontation album. Specifically, the study analyses how the theme of confrontation is conveyed by the artwork of the album cover design. Besides, the study shows linguistically, literarily and by any other aesthetic ways how the theme of confrontation runs through the album. Findings reveal that the artwork of the album cover design speaks volumes without words and is embedded with conscious sophistication in projecting the theme of confrontation. Linguistically, Marley employs deliberate and conscious fiery lexical items inherently confrontational in projecting the theme of confrontation. Literarily, repetition, allusion, pleonasm and metaphors among others play the key role of confrontation in the Confrontation album. Finally, the name of the album, the name of each song and their numerical placement reveal the other aesthetic ways that the theme of confrontation is projected in Marley’s Confrontation, making the album not just a lyrical genius but a discourse masterpiece.